2024
DOI: 10.1039/d4ea00013g
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, humidity, and ionisation effect of iodine oxoacid nucleation

Birte Rörup,
Xu-Cheng He,
Jiali Shen
et al.

Abstract: Iodine oxoacids are recognised for their significant contribution to the formation of new particles in coastal and polar atmospheres. Nevertheless, to incorporate the iodine oxoacid nucleation mechanism into global simulations,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Furthermore, mixed IOPs containing iodic acid and any less acidic species are likely to deprotonate iodic acid, and clusters including sulfuric acid and ammonia have been observed. , Thus, these anionic clusters can also be viewed as likely subunits of larger pure or mixed IOPs. Despite the findings suggesting that iodine oxoacid nucleation is the dominant nucleation pathway above 0.008% relative humidity, another study determined clustering of iodine oxides was still the primary IOP formation pathway even at high relative humidities . Computational results found that clustering between an iodine oxoacid molecule and an I 2 O 4 or I 2 O 5 molecule is energetically favorable and likely enhances the formation of larger iodine oxides, suggesting iodine oxoacids may play an indirect role in IOP formation …”
mentioning
confidence: 94%
“…Furthermore, mixed IOPs containing iodic acid and any less acidic species are likely to deprotonate iodic acid, and clusters including sulfuric acid and ammonia have been observed. , Thus, these anionic clusters can also be viewed as likely subunits of larger pure or mixed IOPs. Despite the findings suggesting that iodine oxoacid nucleation is the dominant nucleation pathway above 0.008% relative humidity, another study determined clustering of iodine oxides was still the primary IOP formation pathway even at high relative humidities . Computational results found that clustering between an iodine oxoacid molecule and an I 2 O 4 or I 2 O 5 molecule is energetically favorable and likely enhances the formation of larger iodine oxides, suggesting iodine oxoacids may play an indirect role in IOP formation …”
mentioning
confidence: 94%